MODEL EXPERIENTIAL LEARNING BERBASIS BERPIKIR KREATIF PADA PEMBELAJARAN MENULIS TEKS NARASI - Isah Cahyani; Resi Amalia; Andoyo Sastromiharjo (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2017)
The focus of the problem studied in this research is the ability to write the narrative of the experimental class students. The purpose of this research is to know the ability of writing learners in experimental class using experiential learning model based on creative thinking. Another purpose of this research is to describe the process of learning to write narrative text by using experiential learning model. The research method used in the form of The matching-only-pretes-postes control group design. The results showed that there was an increase in the average of the results of writing narrative text obtained in the experimental class using experiential learning model with the average value of prates obtained at 61.96, while the average value of pascates of 85.16. It proves that experiential learning model based on creative thinking can improve the ability to write narrative text of students.